THE IMPACT OF NURSE-LED HEALTH PROMOTION AND DISEASE PREVENTION INITIATIVES - Abdullah Maashi Alenezi, Hana Samir Alruwaili, Huda Saud M Aldhfeeri, Mofeedah Nafe Alrawali, Fadyah Nafea Alrowaili, Mureefah Musabah Alsharariy, Maram Aldawi Alruwaili, Hamidah Rajan Aldhafeeri, ,; Afrah Muzil Aldhafeeri, Anwar Sabah Alshammari, Saad Abdullah Alsultan, Huda Abdullah Alhazeem, Amjad Khaled Budookhi, Aysha Faisal Roesain Alnazi, (Chelonian Research Foundation, 2022)
Increasing global research indicates that treatments administered by primary care nurses may help in altering lifestyle risk factors and monitoring chronic illness. So far, there has been a lack of investigation into the possibility and approval of such treatments. The objective is to investigate the viability and reception of nurse-led treatments for managing chronic diseases and reducing lifestyle risk factors in primary care settings, such as general practice or family practice. A comprehensive search was performed in the CINAHL, Medline, and Web of Science databases to locate pertinent material. The methodological quality of the papers was evaluated and data was extracted prior to doing theme analysis. The analysis revealed four main themes: (1) factors that support interventions; (2) obstacles to interventions; (3) satisfaction of consumers; and (4) the role of primary care nurses. Existing literature provides evidence that nurse-led treatments in primary care are both feasible and acceptable for modifying lifestyle risk factors. The long-term viability of these initiatives mostly depends on organizational variables, including money, educational paths, and professional support for the primary care nursing position. Additional rigorous research on treatments by primary care nurses is necessary to enhance the existing body of data.